Avaliação da variação do número de cópias do microssatélite tetralocal DYS503 em populações da África - Lucas Secchim Ribeiro (2010)
The anatomically modern human being, Homo sapiens, is a recent species on the planet and several lines of genetic evidence indicate its unique and recent origin, less than 200,000 years ago in Africa. The expansion of human populations from this continent suffered the founder effect, which occurs when a small group not representative leaves the original population to found a new one, leading to reduced genetic variability of the new group. Thus, a major evidence of human origins is the observation of greater genetic diversity in Africa than in any other continent. However, recent population studies with the tetralocal microsatellite DYS503 revealed a higher Y-chromosome haplotype diversity among white Americans toward blacks Americans. Given the haploid nature and lack of recombination of the Y chromosome, it was investigated the possibility of the individuals from Africa have multiple copies of the microsatellite DYS503, and that the founding population, which left the original group to colonize the rest of the world, had only part of this variability, causing depression of variability as typed by the present alleles. Therefore, a quantitative PCR method was carried out in this study, in which a single pair of primers could simultaneously amplify both products of conserved region near the microsatellite locus and a single copy reference in another chromosome, with different sizes for subsequent analysis automated sequencer. A group of 101 samples of African men from CEPH/HGDP panel was quantified. The results indicate that most individuals have four copies of the genomic block where the microsatellite DYS503 is, and there is no evidence to suggest the existence of individuals with more or less than four alleles in that continent. The construction of the physical map indicates asymmetry between the four copies of the microsatellite, triggering the suspicion of disparate events of chromosomal duplication and deletion. It is therefore possible that other site-specific factors such as high microsatellite mutation rate or deviations of sampling may be acting on this region and generating the unusual drop in variability.